Use of carbonated water in reduction of adjacent gastric activity in 456 consecutive technetium-99m myocardial perfusion imaging studies. (December 2015) - Thomas, Dustin M.; Lee, Joshua S.; Charmforoush, Anthony; Rubal, Bernard J.; Rosenblatt, Stephen A.; Butler, Joshua T.; Clemenshaw, Michael; Cheezum, Michael K.; Slim, Ahmad M.
Background: Small, observational trials have suggested a reduction in adjacent gastric activity with ingestion of soda water in myocardial perfusion imaging (MPI). We report our findings prior to and after implementation of soda water in 467 consecutive MPI studies. Methods: Consecutive MPI studies performed at a high-volume facility referred for vasodilator (VD) or exercise treadmill testing (ETT) were retrospectively reviewed before and after implementation of the soda water protocol. Patients undergoing the soda water protocol received 100 ml of soda water administered 30 min prior to image acquisition and after stress. Studies were performed using a same day rest/stress protocol. Incidence of adjacent gastric activity, diaphragmatic attenuation, stress and rest perfusion defects, and major adverse cardiovascular events (MACE) outcomes defined as death, myocardial infarction, stroke, reevaluation for chest pain, and late revascularization (>90 days from MPI) were abstracted using International Classification of Diseases, Ninth Revision (ICD-9) search. Results: Two hundred and eighteen studies were performed prior to implementation of the soda water protocol and 249 studies were performed with the use of soda water. Baseline demographic data were equal between the groups with the exception of more patients undergoing VD stress receiving soda water ( p < 0.001). Soda water was not associated with a decreased incidence of adjacent gastric activity with stress (54.7% versus 61.9% with no soda water, p = 0.129) or rest (68.6% versus 69.5% with no soda water, p = 0.919) imaging. Less adjacent gastric activity was observed with patients undergoing ETT who received soda water (42.5% versus 56.9% with no soda water, p = 0.031), but no difference was observed between the groups with VD stress (69.0% versus 68.1% with no soda water, p = 1.000). Conclusion: The use of soda water prior to technetium-99m MPI was associated with lower rates of adjacent gastric activity only in patients undergoing ETT stress but not rest or VD stress. This differs from previously published data.